Ecologia da ictiofauna do estuário do rio Paciência, Ilha do Maranhão - Brasil - SILVA JÚNIOR, Milton Gonçalves da (Universidade Federal do Pará, 2013)
Estuarine systems constitute an important habitat for different species of fish. From the ecological standpoint, the ichthyofauna plays an important role in the energy balance between trophic levels in estuarine ecosystems. Thus, the following were aims of the present study: determine the spatiotemporal distribution of the ichtyofauna; explain behavioral and ecological characteristics; compare the composition of relative biomass, ecological and functional guilds in different estuarine systems in northern Brazil; investigate the influence of biotic and abiotic variables and correlations with the biological patterns of the ichthyofauna; and identify changes in the biotic integrity of the tidal creeks studied. Data were acquired through bimonthly sampling in the Iguaiba, Grande and Cristovao tidal creeks between January 2006 and September 2007, using gillnets and block nets. Samples were also taken of the surface water for the determination of physicochemical parameters and dissolved inorganic nutrients. Diversity, evenness and richness indices were employed for the ecological characterization of the species. The biotic integrity index was used to assess the effects of possible environmental changes on the ichthyofauna. Univariate (ANOVA, Kruskall-Wallis) and multivariate (Cluster, nMDS, SIMPER, COIA and ABC curves) statistical methods were used to compare species and capture sites. A total of 12,219 individuals distributed among 55 species and 27 families were caught. The families Sciaenidae, Ariidae, Carangidae, Engraulidae and Mugilidae had the greatest species richness. Ariopsis bonillai and Cetengraulis edentulus made the greatest contribution to the formation of similar groups. Stellifer naso and Cynoscion acoupa were responsible for the dissimilarity between the groups formed. Approximately 66% of the fish caught were juveniles, thereby confirming the use of estuarine systems as nurseries. The records between the Marajoara and Maranhao Gulfs indicate the occurrence of 140 species. Marine occasional visitors and freshwater species occurred occasionally. Marine estuarine-opportunists and estuarine dependents species made the largest contribution to the Maranhão Gulf, whereas estuarine residents species had high biomass values in all estuarine systems investigated. Detritivores occurred mainly in the state of Para and zoobenthivores were found mainly in the state of Maranhao. The occurrence of piscivores was inversely proportional to the abundance of juveniles. The co-structure formed between environment-fish parameters was significant. Salinity, pH, silicate, ammonium, phosphate and nitrate exerted an influence over the structure of the fish community. No species were associated with environments with high concentrations of inorganic nutrients. The ABC curves revealed that the estuarine environment is moderately disturbed and the integrity index characterized the environmental quality of the tidal creeks as very poor to fair. The presence of juveniles demonstrates the importance of tidal creeks to fish development. The ichthyofauna analyzed in the present study exhibits seasonality with regard to hydrological periods. The fish community in tidal creeks can serve as an indicator of the quality of ecosystems submitted to tidal pulses. Therefore, the protection of tidal creeks in mangroves is essential to the management of fishery resources, considering the strong association between ichthyofauna abundance and the structural composition of the habitat.